Katie's Happy Mother's Day - Manushkin, Fran.; Lyon, Tammie (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2015)
When Katie's mother feels unwell on the day before Mother's Day, Katie wants to do everything she can think of to help her mother get well--but she forgot to get a present.
Keywords: Woo, Katie (Fictitious character) -- Juvenile fiction; Chinese Americans -- Juvenile fiction; Mother's Day -- Juvenile fiction; Helping behavior -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Chinese Americans -- Fiction; Mother's Day -- Fiction; Gifts -- Fiction; Helpfulness -- Fiction